Effective Therapy for the Management of Erectile Dysfunction in Men with Diabetes Mellitus: A Review - SATYANAND TYAGI; DR. R.K.ROY (International Journal of Pharma and Bio Sciences, 2010)
Diabetes is a significant cause of erectile and sexual dysfunction. The pathologic processes in diabetes that particularly compromise the responsivity of vascular systems preferentially impact on the vulnerable vascular bed of the penis. About 36% of men with diabetes will experience some degree of erectile dysfunction. Unfortunately, this high-risk population is also difficult to treat. All of the pharmacologic therapies for erectile dysfunction have shown a decrease in efficacy in diabetic patients in comparison with non-diabetic patients. The many strategies for the treatment of erectile dysfunction share an important distinction from most other medical conditions in that the treatment is directed by the choice of the patient and partner. Alprostadil by intracavernous injection has been shown to benefit up to 94% of men with erectile dysfunction and diabetes. Sildenafil will restore the capacity for intercourse in>40% of diabetic patients. More recently two other agents, vardenafil and tadalafil, have been introduced. All the drugs have been shown to be effective across a wide range of aetiologies of erectile dysfunction (ED), including diabetes. The drugs have been shown to improve EF domain scores, penetration and maintenance of erection, resulting in more successful intercourse. Other pharmacologic treatments are available and in development. Ultimately, penile rigidity may be created surgically if the sexual needs of the couple require it.